Effect and safety of drospirenone and ethinylestradiol tablets (II) for dysmenorrhea: A systematic review and meta-analysis - Shi, Jinghua; Leng, Jinhua (Frontiers in Medicine, 2022)
Aim This systematic review aimed to assess the efficacy and safety of Drospirenone and Ethinylestradiol Tablets (II) in the treatment of dysmenorrhea. Methods Electronic databases, namely PubMed, Embase, Cochrane Controlled Register of Trials (CENTRAL), Scopus, Science, CBM, CNKI, Wanfang, and VIP, were searched before September 2022. Randomized controlled trials (RCTs), non-randomized controlled trials, cohort studies, case-control studies, and single-arm studies were included. Furthermore, the Cochrane Risk of Bias Tool for Systematic Reviews version 1 was used for the risk of bias assessment on RCTs. The Risk of Bias In Non-randomized Studies of Interventions (ROBINS-I) tool was used for risk of bias assessment on non-randomized studies. The risk ratio (RR) was calculated for dichotomous data. Mean difference (MD) or standardized MD (SMD) were used as the effect size for continuous data. Results A total of 11 studies involving 2,251 participants with dysmenorrhea were included. When Drospirenone and Ethinylestradiol Tablets (II) conventional 24/4-day regimen was compared with placebo, the total efficiency rate (defined as pain symptom disappearing or being relieved) in Drospirenone and Ethinylestradiol Tablets (II) 24/4-day regimen group was higher than in placebo group (RR = 5.55, 95%CI: 2.48–12.39, P < 0.0001). No clear differences were found on risk of overall adverse events or specific adverse events. When Drospirenone and Ethinylestradiol Tablets (II) was compared with active control drugs, no clear differences were found on the total efficiency rate or visual analog scale (VAS) scores for dysmenorrhea and other related pain. The risk of overall adverse events decreased in Drospirenone and Ethinylestradiol Tablets (II) conventional 24/4-day regimen (13/53 vs. 66/148, RR = 0.55, 95%CI: 0.33–0.91) when compared with active control drugs group. When Drospirenone and Ethinylestradiol Tablets (II) flexible extended regimen was compared with conventional 24/4-day regimen, the number of days of dysmenorrhea (MD=−3.98, 95%CI: −5.69 to −2.27), and dysmenorrhea associated with unscheduled bleedings (MD = −1.6, 95%CI: −2.8 to −0.5), were fewer in flexible extended regimen. In addition, there were no differences found on risk of adverse events (including mood changes, spotting, headache, breast pain, nausea, and vomiting) between compared groups (P > 0.05). Conclusion Drospirenone and Ethinylestradiol Tablets (II) could improve symptoms of dysmenorrhea and decrease other related pain symptoms. More high-quality evidence is needed to confirm the advantages. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021271605], identifier [CRD42021271605].